2007
DOI: 10.1002/hed.20710
|View full text |Cite
|
Sign up to set email alerts
|

Unequal burden of head and neck cancer in the United States

Abstract: Black Americans clearly bear a greater burden from head and neck cancer. The underlying causes are largely unknown, but are most likely due to a complex interplay of differences in access to health care, quality of medical care, biologic/genetic factors, incidence of comorbid conditions, exposure to carcinogens, diet, and cultural beliefs. Prospective studies are needed to define the relative importance of these factors and to inform intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 38 publications
12
124
1
Order By: Relevance
“…These results support the findings of racial disparities that have been previously demonstrated for several other malignancies. [3][4][5][6][7] In the cohort reported herein, AA patients are diagnosed at a younger age and present with more advanced disease. Although they are more likely than whites to undergo chemotherapy and radiotherapy, they are less likely to be operated on for their tumors.…”
Section: Discussionmentioning
confidence: 92%
“…These results support the findings of racial disparities that have been previously demonstrated for several other malignancies. [3][4][5][6][7] In the cohort reported herein, AA patients are diagnosed at a younger age and present with more advanced disease. Although they are more likely than whites to undergo chemotherapy and radiotherapy, they are less likely to be operated on for their tumors.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, the mean age among the three Black patients was 53 years. Interestingly, Goodwin et al recently reported that head and neck cancer incidence and mortality remains greater in Black Americans compared with Whites and peaks at an earlier age (25). Several reasons have been postulated to contribute to the incidence, mortality, survival, and age disparity between Blacks and Whites in terms of head and neck cancer (reviewed in ref.…”
Section: Resultsmentioning
confidence: 99%
“…Several reasons have been postulated to contribute to the incidence, mortality, survival, and age disparity between Blacks and Whites in terms of head and neck cancer (reviewed in ref. 25), but information is scarce pertaining to genetic or epigenetic differences, which may contribute in part to the unequal burden of oral cancer among Blacks. Herein, we report that deletion …”
Section: Resultsmentioning
confidence: 99%
“…HNSCC is a multifactorial disease marked by racial, gender and SES disparities [17]. Biomarker levels may differ based on certain demographic or risk variables [15].…”
Section: Discussionmentioning
confidence: 99%